2007
DOI: 10.1038/nature06308
|View full text |Cite
|
Sign up to set email alerts
|

A dual-Ca2+-sensor model for neurotransmitter release in a central synapse

Abstract: Ca2+-triggered synchronous neurotransmitter release is well described, but asynchronous release-in fact, its very existence-remains enigmatic. Here we report a quantitative description of asynchronous neurotransmitter release in calyx-of-Held synapses. We show that deletion of synaptotagmin 2 (Syt2) in mice selectively abolishes synchronous release, allowing us to study pure asynchronous release in isolation. Using photolysis experiments of caged Ca2+, we demonstrate that asynchronous release displays a Ca2+ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
520
2
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 333 publications
(571 citation statements)
references
References 45 publications
31
520
2
7
Order By: Relevance
“…Members of the synaptotagmin (Syt) protein family that localize to vesicles function as Ca 2ϩ sensors that couple Ca 2ϩ rises to vesicle exocytosis (Chapman, 2002;Sudhof, 2004;Rizo et al, 2006). Syt-1 is the best understood isoform and functions as a synaptic vesicle Ca 2ϩ sensor for the rapid synchronous release (Geppert et al, 1994) but not for the slow asynchronous release of neurotransmitter (Sun et al, 2007) in hippocampal neurons. Syt-2 and -9 likely play similar roles at other synapses (Xu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Members of the synaptotagmin (Syt) protein family that localize to vesicles function as Ca 2ϩ sensors that couple Ca 2ϩ rises to vesicle exocytosis (Chapman, 2002;Sudhof, 2004;Rizo et al, 2006). Syt-1 is the best understood isoform and functions as a synaptic vesicle Ca 2ϩ sensor for the rapid synchronous release (Geppert et al, 1994) but not for the slow asynchronous release of neurotransmitter (Sun et al, 2007) in hippocampal neurons. Syt-2 and -9 likely play similar roles at other synapses (Xu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The in vivo study in his lab demonstrated that Syt1 knockout abolished the fast synchronous transmitter release and the mutation that changes the calcium affinity of endogenous Syt1 also altered the calcium-dependent synchronous neurotransmitter release to the same extent [3032]. These conclusions were reached based on the fact that the synaptotagmin knock-out/mutations caused neither impairment in calcium influx into the nerve terminal nor the disturbance of the spatial coupling between calcium channels and vesicles [32]. Furthermore, they found that only three synaptotagmins-Syt1, Syt2 and Syt9-mediate fast synaptic vesicle exocytosis.…”
mentioning
confidence: 81%
“…Only these isoforms of synaptotagmin were able to rescue the fast synchronous component of transmitter release in syt-1 deficient neurons [33]. All the results lead to the plausible mechanism that synaptotagmin functions as the calcium sensor and once calcium-binding sites of Synaptotagmin C 2 domain are occupied, the calcium-activated synaptotagmin interacts with SNARE complex, thereby triggering synaptic vesicle fusion [32].…”
mentioning
confidence: 86%
“…PTP in wild-type mice is similar to that observed in rats ( Figure 6E, left). In synaptotagmin-II knockout mice, however, EPSC and mEPSC potentiation disappeared following stimulation, which strongly suggests that synaptotagmin-II is required for PTP [24,31] (Figure 6E, right). When EGTA was added to the extracellular solution to buffer calcium, PTP and mEPSC potentiation disappeared, further confirming the requirement of calcium [24] .…”
Section: Compound Vesicle Fusion and Bulk Endocytosismentioning
confidence: 98%
“…Furthermore, the mEPSC measured from the postsynaptic cells showed no large events, indicating a small quantal size ( Figure 6D, bottom). Synaptotagmin is an immediate calcium sensor that mediates calcium-dependent exocytosis, and in the calyx of Held, synaptotagmin-II mediates this rapid fusion event [31] . These results together suggest that, similarly to regular fusion events, compound fusion requires synaptotagmin.…”
Section: Compound Vesicle Fusion and Bulk Endocytosismentioning
confidence: 99%